Long-gap esophageal atresia: a single center experience - Liu, Xiaoshu; Sun, Xue; Ren, Hongxia (Frontiers in Pediatrics, 2025)
ObjectiveTo summarize the treatment experience and individualized treatment strategies for children with long-gap esophageal atresia (LGEA) at a single center.MethodsThe clinical data of children with LGEA admitted to Shanxi Provincial Children's Hospital from January 2018 to December 2024 were collected and analyzed. The data included classification, gap length, timing of surgery, methods of esophageal elongation, methods of esophageal anastomosis, postoperative complications, prognosis, etc.ResultsA total of 7 children with LGEA were studied, with 3 males and 4 females. Among them, 6 cases were Type I esophageal atresia (EA), 1 case was Type II EA. The average distance between the blind ends of the esophagus was approximately (5.36 ± 0.75) cm. All 7 cases were followed up completely, with 5 cases achieving full recovery, 1 cases having poor prognosis, and 1 cases resulting in death. The overall mortality rate was 14.28% (1/7). Type I EA had 6 cases, with the esophageal blind ends approximately (5.25 ± 0.76) cm apart during the neonatal period. All underwent staged surgery: stage I involved gastrostomy during the neonatal period, and stage II involved esophageal anastomosis, gastric replacement esophagectomy, or colonic replacement esophagectomy. The average age at stage II surgery was (210.83 ± 115.75) days. Type II EA had 1 case, with the esophageal blind ends approximately 6 cm apart during the neonatal period. Staged surgery was performed: Stage I, gastrostomy during the neonatal period; Stage II, esophageal-tracheal fistula ligation and intra-thoracic esophageal traction at both ends; Stage III, esophageal anastomosis.ConclusionThe treatment of LGEA is still challenging, good treatment results can be obtained by formulating a personalized treatment plan, selecting an appropriate surgical method, delaying anastomosis, preserving the original esophagus as much as possible, strengthening perioperative management, and establishing long-term follow-up.